Effect of advertising content and key opinion leaders on consumer's visit intentions to Novotel Bogor Golf Resort - Yuwantiningrum, Sri Endah; Basri, Djahra Dwi; Rainanto, Bambang Hengky; bin Bon, Abdul Talib; Van Melle, Jonathan; Meledge-Ade, Victor; Rudyanto, Bambang (Universitas Merdeka Malang, 2025)
In the digital era, marketing strategies have evolved to include digital content and Key Opinion Leaders (KOLs) to enhance consumer engagement. Advertising content, which aims to inform and engage, helps shape perceptions of products or services, while KOLs—social media influencers—play a significant role in influencing public opinion and consumer decisions. Both elements are essential in competitive industries, such as hospitality. This study explores the impact of advertising content and KOLs on consumer interest in visiting Novotel Bogor Golf Resort & Convention Center. A quantitative approach was used, distributing questionnaires to 100 respondents, including potential customers and previous guests. Data analysis was conducted with SmartPLS, covering validity, reliability, and hypothesis testing. The results show that advertising content has a positive effect on visit interest, but it is statistically insignificant. In contrast, the influence of KOLs is both positive and statistically significant, indicating that KOLs are more effective in attracting consumer interest. Their closer interaction with audiences and ability to deliver authentic, visually engaging content, particularly in videos, significantly enhance consumer engagement.